IMPLEMENTING THE TOTAL PHYSICAL RESPONSE METHOD WITH WORD WALL PICTURE TO INCREASE DEAF STUDENTS’ VOCABULARY IN THE FIRST GRADE OF SMP LUAR BIASA NEGERI MARTAPURA - Harpiansi Harpiansi; Fatimah Kesuma Astuti (Journal of English Educational Study (JEES), 2019)
Abstract : This research aimed to increase the English vocabulary mastery of the deaf students, especially in the material of instruction by using the total physical response method with word wall picture in the first grade of SMP Luar Biasa Negeri Martapura in the academic year of 2014/2015. The subject of this research consisted of 9 students. The method used in this research was Classroom Action Research (CAR) designed based on the model proposed by Kemmis and McTaggart. This research was conducted in three cycles, in which for each cycle consisted of 3 meetings. It consisted of a planning phase, acting, observing, and reflecting. To answer the research questions, qualitative and quantitative were collected. The qualitative data were obtained through observation, while the quantitative data were obtained through tests and a questionnaire. The result showed there was an increase of the deaf students’ English vocabulary mastery. The pre-cycle test mean score was 48.89, while the mean score in the test of cycle 1, cycle 2, and cyle 3 was respectively 56.67, 63.89, and 78.89. So, the criteria of success had been achieved. The data obtained through the questionnaire showed there was a positive response given by the students in the teaching-learning process of English vocabulary using the total physical response method with word wall picture. In which the mean score of the pre-questionnaire was 32.22%. Then the mean of the post-questionnaire was 77.04%, so it increased as much as 44.82%. Furthermore, the results of observation showed that deaf students were motivated in the teaching-learning process during the implementation of total physical response method with word wall picture. Keywords: Total physical response, word wall picture, vocabulary mastery, deaf students, and classroom action research.